Cultural Guidelines for Commercial Production of Interiorscape Fire Flash (Chlorophytum amaniense): ENH998/EP253, rev. 6/2014 - Chen, J.; McConnell, D. B.; Henny, R.J. (EDIS, 2014)
This document is about 'Fire Flash' (Chlorophytum amaniense). This is a foliage plant introduced to Florida from Thailand in the late 1990s. Bright coral petioles and midveins contrast with deep green, ovate-lanceolate leaves making an exotic appearing and exciting new plant (Chen et al. 2002). Like spider plant (Chlorophytum comosum), fire flash is a member of the family Liliaceae, but actually originates from the rainforests of East Africa in the Usambara Mountains of Tanzania. 'Fire Flash' is the only recognized cultivar in this species; other names have been given to it including 'Mandarin Plant' and 'Tangerine'. This article is intended to provide brief guidelines for propagation, production, and interior use of 'Fire Flash' and list common problems that may be encountered during production and interiorscape use.